Barriers to Physical Activity Among African American Women: An Integrative Review of the Literature - Joseph, Rodney P. (Women Health, 2015)
A key aspect for researchers to consider when developing culturally appropriate physical activity (PA) interventions for African American (AA) women are the specific barriers AA women face that limit their participation in PA. Identification and critical examination of these barriers is the first step in developing comprehensive culturally relevant approaches to promote PA and help resolve PA-related health disparities in this underserved population. We conducted a systematic integrative literature review to identify barriers to PA among AA women. Five electronic databases were searched, and 42 studies (27 qualitative, 14, quantitative, 1 mixed method) published since 1990 (Range 1998–2013) in English language journals met inclusion criteria for review. Barriers were classified as intrapersonal, interpersonal, or environment/community according to their respective level of influence within our social ecological framework. Intrapersonal barriers included: lack of time, knowledge, and motivation; physical appearance concerns; health concerns; monetary cost of exercise facilities; and tiredness/fatigue. Interpersonal barriers included: family/caregiving responsibilities; lack of social support; and lack of a PA partner. Environmental barriers included: safety concerns; lack of facilities; weather concerns; lack of sidewalks; and lack of physically active AA role models. Results provide key leverage points for researchers to consider when developing culturally relevant PA interventions for AA women.